Adiponectin concentration after a body mass reduction in a group of premenopausal obese women living in Lima, Peru - García-Quispes, Wilser Andrés (2019)
Objective: To investigate the changes in the plasma-circulating adiponectin concentration in 23 premenopausal obese women living in Lima after a body mass reduction as a result of an aerobic physical activity program and a low-calorie diet. Materials and methods: An analytical and quasi-experimental study was conducted in a group of obese women. In addition, another 24 women were considered as control or reference group for comparing their adiponectin concentration and other biochemical markers. The quantification of adiponectin was carried out using the ELISA test. Fasting blood glucose concentration, cholesterol, high-density lipoprotein and triglycerides levels were quantified by routine clinical analysis. Results: Before beginning the program, the control group showed high adiponectin levels (median, 8.54 µg/mL; range, 6.14 µg/ mL to 13.49 µg/mL) compared to the obesity group (median, 7.03 µg/mL; range, 3.77 µg/mL to 17.23 µg/mL). However, the difference was not statistically significant (P = 0.0563). Once the program was finished, the obesity group showed a statistically significant reduction in the body mass index (P = 5.98e-08) and abdominal circumference (P = 1.55e-08), and a statistically significant increase in the adiponectin levels (median, 8.79 µg/mL; range, 5.50 µg/mL to 19.37 µg/mL) (P = 0.0127). Conclusions: Based on the results, we conclude that the adiponectin concentration in premenopausal obese women increases when the body mass is reduced as a result of aerobic physical activity and a low-calorie diet.